2017
DOI: 10.1371/journal.pone.0179804
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and microsimulation techniques on the prognosis of dementia: A systematic literature review

Abstract: BackgroundDementia is a complex disorder characterized by poor outcomes for the patients and high costs of care. After decades of research little is known about its mechanisms. Having prognostic estimates about dementia can help researchers, patients and public entities in dealing with this disorder. Thus, health data, machine learning and microsimulation techniques could be employed in developing prognostic estimates for dementia.ObjectiveThe goal of this paper is to present evidence on the state of the art o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 73 publications
1
48
0
Order By: Relevance
“…In terms of dementia diagnosis, there have been increasing applications of various machine learning approaches, most commonly with imaging data for diagnosis and disease progression [11]. This includes amyloid PET imaging [12], MR imaging [13] and combined PET and MR imaging [14].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of dementia diagnosis, there have been increasing applications of various machine learning approaches, most commonly with imaging data for diagnosis and disease progression [11]. This includes amyloid PET imaging [12], MR imaging [13] and combined PET and MR imaging [14].…”
Section: Introductionmentioning
confidence: 99%
“…Being able to work with large amounts of multifactorial data, machine learning technology could be beneficial in the investigation of prognostic estimates for dementia. However, after a systematic literature review that explored machine learning approaches for prognosis [14], it was concluded that, based upon 37 primary studies, the research has been very focused on neuroimaging for identifying and validating biomarkers in the brain to predict the development of dementia from its prodromal stage, i.e., mild cognitive impairment (MCI), and usually in a time frame of 3 years [14]. These studies scarcely considered modifiable risk factors.…”
Section: Machine Learning Approaches For the Prognosis Of Dementiamentioning
confidence: 99%
“…In their review, Dallora and colleagues (Dallora et al 2017) found that for the prognosis of dementia, the most applied ML technique is SVM; among ML, neuroimaging studies (i.e. MRI and PET) were most frequent compared to cognitive/ behavioural, genetic, lab tests and demographic data with the main of predicating the proportion of MCI individuals that will develop AD.…”
Section: Current Application: From Dementias To Parkinson's Diseasementioning
confidence: 99%
“…The researchers in terms of validation procedure, datasets used, number or records within the same dataset and follow-up period found limitations. However, defining biomarkers in the field of neurodegenerative diseases could improve diagnosis and treatment and consolidate the role of precision medicine and prediction of disease progress (Dallora et al 2017;Reitz 2016;Rosenberg 2017). As we have seen, technologies (and eHealth especially) could be a good instrument, also in the context of the P5 approach and future medicine.…”
Section: Current Application: From Dementias To Parkinson's Diseasementioning
confidence: 99%